Motivational Mechanisms Underlying Second Language Achievement: A Regulatory Focus Perspective. Issue 2 (5th January 2021) - Papi, Mostafa; Khajavy, Gholam Hassan
Abstract: We tested a theoretical model that integrated regulatory focus, second language (L2) self‐guides, anxiety and enjoyment, eager and vigilant L2 use, and L2 achievement. We collected data from 324 students learning English as a foreign language. Structural equation modeling results showed that (a) the promotion focus positively predicted ideal selves, whereas the prevention focus negatively predicted ought selves; (b) ideal self/own predicted enjoyment positively and anxiety negatively, ought self/other and ideal self/other predicted anxiety positively, and ought self/own positively predicted vigilant L2 use; (c) enjoyment predicted eager L2 use positively and vigilant L2 use negatively, whereas anxiety predicted vigilant L2 use positively; and finally (d) eager L2 use positively and vigilant L2 use negatively predicted achievement. The findings suggest that a promotion‐oriented approach to language learning and teaching might lead to more adaptive motivational, emotional, and behavioral patterns, which in turn contribute to language learning success. Theoretical and educational implications are discussed. Abstract :